The kinesics communication education of pre-service speech therapists’ teacher - López Salas, M. Sc. Déborah Magaly; Gómez Cardoso, Dr. C. Ángel Luis; Puebla Caballero, M. Sc. Nely del Milagro (Transformación, 2021)
Objective: This paper aims at describing a didactic strategy to training kinesics communication in aimed at treatment in speech therapists’ teacher. Methods: The authors rely on research methods such as analysis and synthesis, logical and historical review, interviews, surveys, documentary review and the percentage analysis as a descriptive statistical procedure. Result: The main finding is precisely the didactic strategy aimed at educating kinesics communication education of pre-service speech therapists’ teacher. Conclusions: The kinesics nonverbal communication in pre-school children is necessary for the early identification of language disorders and for understanding the bases supporting its use as an alternative communication variant. The historical analysis of the curriculum and the findings of an initial diagnosis, allowed to devise a didactic strategy for this purpose.